2020
DOI: 10.22201/fi.25940732e.2020.21n1.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación térmica de material compuesto de cemento portland reforzado con agregado fino de CBC y FO tratada con Silano

Abstract: El uso de fibras naturales (yute, coco, caña, etcétera.) y desechos agroindustriales (ceniza, cascarilla de arroz, etcétera) como materiales de refuerzo en la obtención de materiales compuestos ha ido en aumento, debido a que se consideran de bajo costo y fácil obtención. Se han estudiado las interacciones de los materiales de refuerzo, así como las propiedades físicas, químicas y mecánicas que le transfieren al material. En esta investigación se desarrolló un material con una matriz de cemento portland compue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The mean thermal [55] found thermal conductivity values for ferrocement of 0.69 W/m K, ferrocement plus coconut fiber 0.221 W/m K, lightweight concrete brick 0.53 W/m K, hollow concrete block 0.68 W/m K and red clay brick 0.93 W/m K. Ruiz Torres et al [59] reported thermal conductivity for thermos-slab 0.263 W/m K, cement-sand mortar 0.63 W/m K, typical annealed red brick 0.872 W/m K. Borbón Almada et al [60] reported a thermal conductivity for annealed mud brick 0.814 W/m K, lightened block 0.465 W/m K, cement-sand mortar 0.470 W/m K and recycled cement-sand mortar 0.291 W/m K (recycled material from concrete demolition). Rico Rodríguez et al [61] reported a value of 0.21 W/m K in the thermal conductivity of a cement composite material reinforced with bagasse ash and fiber. In this context, the thermal conductivity value of 0.2008 W/mÁK of the PO + CE panel proposed in this study has a low thermal conductivity suitable for thermal applications in construction.…”
Section: Results Of Thermal Conductivitymentioning
confidence: 99%
“…The mean thermal [55] found thermal conductivity values for ferrocement of 0.69 W/m K, ferrocement plus coconut fiber 0.221 W/m K, lightweight concrete brick 0.53 W/m K, hollow concrete block 0.68 W/m K and red clay brick 0.93 W/m K. Ruiz Torres et al [59] reported thermal conductivity for thermos-slab 0.263 W/m K, cement-sand mortar 0.63 W/m K, typical annealed red brick 0.872 W/m K. Borbón Almada et al [60] reported a thermal conductivity for annealed mud brick 0.814 W/m K, lightened block 0.465 W/m K, cement-sand mortar 0.470 W/m K and recycled cement-sand mortar 0.291 W/m K (recycled material from concrete demolition). Rico Rodríguez et al [61] reported a value of 0.21 W/m K in the thermal conductivity of a cement composite material reinforced with bagasse ash and fiber. In this context, the thermal conductivity value of 0.2008 W/mÁK of the PO + CE panel proposed in this study has a low thermal conductivity suitable for thermal applications in construction.…”
Section: Results Of Thermal Conductivitymentioning
confidence: 99%